1) 5+4x = 6+3x
4x-3x = 6-5
x = 1
2) 5x-3 = 3x+1
5x-3x = 1+3
2x = 4
x = 2
3) -8+2x = x-5
2x-x = -5+8
x = 3
4) 9-3x = 1+x
-3x-x = 1-9
-4x = -8
x = 2
5) 6x - 7 = 8 + 3x
6x-3x = 8+7
3x = 15
x = 5
6) 4x - 2 = 10 +2x
4x-2x = 10+2
2x = 12
x = 6
7) 3-4x = 17-6 x
-4x+6x = 17-3
2x = 14
x = 7
8) 9x-1 = 8x+7
9x-8x = 7+1
x = 8
9) 4x-6 = 2x+12
4x-2x = 12+6
2x = 18
x = 9
10) 3x+3 = 2x+13
3x-2x = 13-3
x = 10
11) 9-3x = 20-4x
-3x+4x = 20-9
x = 11
12) 7x-1 = 5x+23
7x-5x = 23+1
2x = 24
x = 12
13) 2-3x = 28-5x
-3x+5x = 28-2
2x = 26
x = 13
14) 6x+3 = 5x+17
6x-5x = 17-3
x = 14
15) 8x-10 = 6x+20
8x-6x = 20+10
2x = 30
x = 15
16) 17x-1 = 15+16x
17x-16x = 15+1
x = 16
17) 19+3x = 5x-15
3x-5x = -15-19
-2x = -34
x = 17
18) 6+2x = 4x-30
2x-4x = -30-6
-2x = -36
x = 18
19) 5x+3 = 4x+22
5x-4x = 22-3
x = 19
20) 2+2x = x+24
2x-x = 24-2
x = 22
21) 5+7x = 26+6x
7x-6x = 26-5
x = 21
Удачи!
Пошаговое объяснение:
х^2+2х+х+2=х^2+4х-3х-12
х^2+3х+2-х^2-4х+3х+12=0
2х+14=0
2х=-14
х=-14÷2
х=-7
6х^2+21х-2х-7-6х^2+5х-6х+5-16=0
18х-2-16=0
18х-18=0
х=18÷18
×=1
24-12у^2+15у-4у+5-22у+11+12у^2-6у-6=0
-17у+34=0
-17у=-34
у=34÷17
у=2
30у-6у^2+10-2у=47-6у^2+2у+9у-3
28у-6у^2+10-47+6у^2-2у-9у+3=0
17у=34
у=34÷17
у=2